2012
DOI: 10.1021/jp210791j
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hofmeister Cations at Negatively Charged Hydrophilic Surfaces

Abstract: This work explores the interactions of cations with highly negatively charged solid/aqueous interfaces. Vibrational sum frequency spectroscopy (VSFS) was exploited to observe interfacial water structure on the surfaces of fused quartz and titanium dioxide (TiO 2 ) in the presence of nine chloride salts with different alkali, alkaline earth, and transition metal cations. The results showed prominent specific cation effects at low concentration. The cations followed a direct Hofmeister series. On quartz surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
146
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(162 citation statements)
references
References 58 publications
10
146
1
5
Order By: Relevance
“…It is well accepted that electrolytes bring interfacial disorder, as evidenced by the intensity shrink of the ice-like vibrational signatures, which in turn shows the disappearance of the strong H-bonds formed by interfacial water molecules. At the fused quartz/water interface, it has been shown that SFG intensities depend on the nature of both cations 13 and anions. 14 From the spectroscopic results, cations with higher surface charge densities induce the largest SFG intensity weakening: such large perturbation on interfacial water may thus indicate that, for instance, Na + comes closer to the surface than Cs + .…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is well accepted that electrolytes bring interfacial disorder, as evidenced by the intensity shrink of the ice-like vibrational signatures, which in turn shows the disappearance of the strong H-bonds formed by interfacial water molecules. At the fused quartz/water interface, it has been shown that SFG intensities depend on the nature of both cations 13 and anions. 14 From the spectroscopic results, cations with higher surface charge densities induce the largest SFG intensity weakening: such large perturbation on interfacial water may thus indicate that, for instance, Na + comes closer to the surface than Cs + .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The surface structure of these particles has been previously studied by in-situ 29 Si NMR and no evidence of surface bound polymeric brushes were seen, 36 5 frequency generation study on the effects of cations at the water-silica and water-titania (TiO 2 ) interfaces. 28 Potentiometric Titrations. Surface charge densities (SCDs) are determined by potentiometric titration using a Mettler-Toledo G20 Compact Titrator equipped with a Mettler-Toledo Expert electrode and an electronic controlled rod stirrer (70% polypropylene and 30% fiberglass).…”
Section: Introductionmentioning
confidence: 99%
“…7 Depending on the molecular context, the hydration properties of ammonium can vary somewhat, but in general it behaves similar to larger alkali cations. 8 In contrast, the guanidinium functionality can be found on either of the extreme sides of the Hofmeister series depending on the particular process under investigation.…”
mentioning
confidence: 99%